Relationships between work-status and leisure lifestyle at the age of 60 years old - Rennemark, Mikael (Eur J Ageing, 2006)
The tendency to leave work before the formal pension age is reached has increased in most OECD-countries. The societal economical consequences of these circumstances are worrying and knowledge about the mechanisms behind this trend is urgent. Previous research has focused on the role of pension rules, work environments, health and education. In this study, it was investigated if there are differences in personality and in leisure lifestyle between individuals who have retired at the age of 60 and individuals who still work at the same age. The effects of health, work satisfaction, education level and household economy were taken into account. The sample was drawn from the SNAC-Blekinge database and the participants were 184 randomly selected individuals aged 60 years. The variables were measured using standardised questionnaire data. The results show that early retirement due to health problems was negatively related to visiting museums and art expositions and positively related to number of symptoms of disease. Retirement due to other reasons than disability was negatively related to reading books and to number of symptoms. The study suggests there is a possible stress-reducing effect of participation in cultural/intellectual activities. This effect may strengthen the ability and motivation to continue working at the age of 60 years old.